2010
DOI: 10.1038/sj.bdj.2010.1132
|View full text |Cite
|
Sign up to set email alerts
|

The use of flumazenil after midazolam-induced conscious sedation

Abstract: Incident 8-Incomplete reversal During IVS procedure pt re-sedated. Flumazenil given at 1420-flumazenil has a shorter half-life than midazolam. Pt woke for about 40 minutes then re-sedated. SATS initially normal (brought back from waiting room to surgery). Dentist went for advice from Day Surgery Unit while Dental Nurse managed SPO2 drop by managing airway. Pt recovered consciousness shortly afterwards.' 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
2
9
0
Order By: Relevance
“…Although the RRR suggested that administration of flumazenil is indicative of a benzodiazepine overdose, its use in dentistry is for reasons other than to reverse respiratory depression as indicated in all our data, supporting earlier findings (23). Flumazenil can prevent sedation-related accidents after dental procedures in those with mobility problems and severe learning disabilities, who have been shown to be at an increased risk of falls and injury (24).…”
Section: Discussionsupporting
confidence: 87%
“…Although the RRR suggested that administration of flumazenil is indicative of a benzodiazepine overdose, its use in dentistry is for reasons other than to reverse respiratory depression as indicated in all our data, supporting earlier findings (23). Flumazenil can prevent sedation-related accidents after dental procedures in those with mobility problems and severe learning disabilities, who have been shown to be at an increased risk of falls and injury (24).…”
Section: Discussionsupporting
confidence: 87%
“…Flumazenil, a benzodiazepine receptor antagonist, effectively reverses benzodiazepine-induced CNS depression via competitive inhibition at the GABA-A receptor-binding site [2][3][4][5][6][7][8]. Flumazenil has been beneficial for expediting patient recovery from anesthesia [9][10][11] and was previously studied in 519 patients at our center; of which, 15 were diagnosed with alcohol withdrawal [12].…”
Section: Introductionmentioning
confidence: 99%
“…Flumazenil is a specific benzodiazepine competitive antagonist, which inhibits the central effects of benzodiazepine agonists. Flumazenil is well-tolerated across a wide range of doses and has little side effects ( 38 , 39 ). Furthermore, flumazenil administration following alfaxalone-midazolam anesthesia significantly shortened recovery time and increased recovery quality in R. aegyptiacus in comparison to saline control ( 25 ).…”
Section: Discussionmentioning
confidence: 99%